DISTRIBUTED MODEL TERMINAL SERVER USING THE SOFTWARE PRODUCT "1C Enterprise 8.x" - , С. И., Н. И. (Municipal economy of cities. Series: «Economy science», 2013)
The model distributed terminal server is considered. It is proposed division of the basic model of the terminal server into two separate pavilion equipment and software object.